Enhancing basketball players’ jump shooting performance and neuroplasticity, kinematic optimization through flash reflex-based sensory-motor perception and balance - Ahmed K. Hassan (Scientific Reports)
Abstract This study investigates the efficacy of proprioceptive and motor balance training using quick reflexes in improving jumping and shooting performance, neuroplasticity, and kinematic variables among basketball players. A total of 32 participants were divided into two equal groups: an experimental group of 16 players with an average age of 18.84 years and a control group of 16 players with an average age of 19.03 years. The experimental group underwent training involving proprioceptive and motor balance exercises with blink reflex stimulation, while the control group followed standard training routines. Post-intervention assessment revealed significant neurological plasticity and improvements in the key variables related to jump shooting performance in the experimental group compared to the control group (p < 0.001). This shows that proprioceptive and motor balance training with saccade stimulation enhances jump shooting skills and kinematic attributes related to shooting in basketball players. This adds to the emerging evidence on the diverse alternative training strategies that can improve athletic performance, thus providing important historical context for future studies as well as practical applications in sports training.